2014
DOI: 10.1108/s2050-206020140000008019
|View full text |Cite
|
Sign up to set email alerts
|

Should I Text or Should I Call?: How College Students Navigate Mediated Connections with Family

Abstract: Purpose À This study investigated how college students' pace of life and perceptions of communication technologies shape the choices they make when engaging in mediated communication with their parents.Methodology À We conducted 21 interviews to explore how students' understandings of various communication technologies, the rules and patterns of technology use in their families, and the circumstances surrounding their use of technologies while at college influence the number and type of media they use to commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Using an ecological momentary assessment design, our own research suggests that phone contacts between younger adolescents and parents, though somewhat infrequent, include responding to adolescent mental health needs with both monitoring and support . For emerging adults, qualitative interviews (Platt et al 2014), focus groups (Chen and Katz 2009), and quantitative self-report surveys (Ramsey et al 2013;Miller-Ott et al 2014) highlight that digital communication plays a key role in maintenance and evolution of a positive, connected parent-child relationship in the college years. Yet, the way in which positive connection as well as monitoring and disclosure behaviors are enacted as dyadic processes within digital communication between parents and their emerging adults remains to be charted as does the importance of these virtual interactions in supporting autonomy and relatedness in emerging adults.…”
Section: Parent-emerging Adult Positive Connection and Monitoring And Disclosing Behaviors Via Mobile Phonementioning
confidence: 99%
“…Using an ecological momentary assessment design, our own research suggests that phone contacts between younger adolescents and parents, though somewhat infrequent, include responding to adolescent mental health needs with both monitoring and support . For emerging adults, qualitative interviews (Platt et al 2014), focus groups (Chen and Katz 2009), and quantitative self-report surveys (Ramsey et al 2013;Miller-Ott et al 2014) highlight that digital communication plays a key role in maintenance and evolution of a positive, connected parent-child relationship in the college years. Yet, the way in which positive connection as well as monitoring and disclosure behaviors are enacted as dyadic processes within digital communication between parents and their emerging adults remains to be charted as does the importance of these virtual interactions in supporting autonomy and relatedness in emerging adults.…”
Section: Parent-emerging Adult Positive Connection and Monitoring And Disclosing Behaviors Via Mobile Phonementioning
confidence: 99%
“…Research has found that college students use a range of digital technologies, such as texting, phone calls, video calls, and social media, to maintain communication with their families (Hussong et al, 2021). Some of the most widely cited reasons for this frequent digital communication in college is simply the efficiency and convenience, especially when these students are physically distant from their families (Platt et al, 2014). Digital communication between college students and their families has also been shown to play a vital role in allowing students to maintain emotional closeness and receive support from their families (Jensen et al, 2021).…”
Section: Emerging Adult Digital Communication With Familymentioning
confidence: 99%
“…Diversifying the technologies used to keep in touch with one's parents may also be helpful for some emerging adults, particularly if their parents' communication competence is lower than average (Schon, 2014). Developing a more diverse communication repertoire may also aid emerging adults in establishing a stronger sense of individual identity, as they begin to assert their technology preferences and search for ICTs that are most compatible with the new circumstances of college life (Platt et al, 2014). Our study seeks to understand how emerging adults make and understand these choices in relation to the autonomy-connection dialectic.…”
Section: Technology Use In Familiesmentioning
confidence: 99%